1989
DOI: 10.1002/yea.320050310
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequencing of the gene for apocytochrome b of the yeast Kluyveromyces lactis strains WM27 (NRRL Y‐17066) and WM37 (NRRL Y‐1140)

Abstract: The apocytochrome b genes from two strains of the yeast Kluyveromyces lactis, have been isolated and sequenced. The coding sequences in strains WM27 (NRRL Y-17066) and WM37 (NRRL Y-1140) were identical but the upstream noncoding regions were slightly different. The sequences demonstrated the presence of a continuous open reading frame with no introns. The amino acid sequence, derived from the coding strand, showed 82% homology to the apocytochrome b of Saccharomyces cerevisiae strain D273-10B and only 58% homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The boundartes of the conserved domains in cytochrome b that were assigned prev]ously [6,27,33] are largely confirmed m the current ahgnment of sequences (Fig 3) We have evaluated the different degree of conservation of the structural elements of the protein by measuring their average score of identity m the ahgnment of This consensus sequence has been generated by using the alignment of Fig 2 normahzed to the yeast sequence (gaps or insertions have been excluded) and extended to the following sequences to increase the variation /~ lac.s [198], C glabrata (G D Clark-Walker, personal communication). N crassa [200], A franclscana (R Garesse and F Marco, personal communication), T brucet [48,49], S purpuratus [45].…”
Section: Iii-c the Most And Least Conserved Regtons In Cytochrome Bmentioning
confidence: 84%
“…The boundartes of the conserved domains in cytochrome b that were assigned prev]ously [6,27,33] are largely confirmed m the current ahgnment of sequences (Fig 3) We have evaluated the different degree of conservation of the structural elements of the protein by measuring their average score of identity m the ahgnment of This consensus sequence has been generated by using the alignment of Fig 2 normahzed to the yeast sequence (gaps or insertions have been excluded) and extended to the following sequences to increase the variation /~ lac.s [198], C glabrata (G D Clark-Walker, personal communication). N crassa [200], A franclscana (R Garesse and F Marco, personal communication), T brucet [48,49], S purpuratus [45].…”
Section: Iii-c the Most And Least Conserved Regtons In Cytochrome Bmentioning
confidence: 84%
“…There exist, however, cases of notable polymorphic difference. Coria et al [35,36] and Brunner et al [37] have reported changes of restriction sites and a sequence translocation in the strain WM 27 (a clone of NRRL Y‐1118 = CBS 6315, which is supposed to be one of the parents of the strain W600B, which in turn is the source of ade1 , ade2 and leu1 markers carried by many laboratory strains). These variations may be taken into account in the exploitation of the genomic sequence data of the strain Y‐1140 (CBS2359).…”
Section: Resultsmentioning
confidence: 99%
“…However, yeasts show a paucity of mitochondrial genes, which in some species is compensated for by a structural complexity in the intergenic regions, resulting from the distribution of optional introns (Wilson & Fukuhara, 1991 ;Hardy & Clark-Walker, 1991 ;Clark-Walker & Weiller, 1994), rearrangements and\or insertions\deletions that encompass entire genes (Hardy et al, 1989 ;Wilson et al, 1989 ;Hoeben et al, 1993 ;Pis) kur et al, 1998), together with a complex pattern of changes from the universal code of codon usage (Brunner & Coria, 1989 ;ClarkWalker & Weiller, 1994).…”
Section: Belloch and Othersmentioning
confidence: 99%